Physical examinations via video? Qualitative study of video examinations in heart failure, using conversation analysis - Seuren, LM; Wherton, J; Greenhalgh, T; Cameron, D; A'Court, C; Shaw, SE (Journal of Medical Internet Research, 2020)
Background: Video consultations are increasingly seen as a possible replacement for face-to-face consultations. Direct physical examination of the patient is impossible; however, a limited examination may be undertaken via video (eg, using visual signals or asking a patient to press their lower legs and assess fluid retention). Little is currently known about what such video examinations involve.